Exercise and chronic disease an evidence-based approach - Saxton, John (Routledge, 2011)
It is now widely accepted that there are important links between inactivity and lifestyle-related chronic diseases, and that exercise can bring tangible therapeutic benefits to people with long-term chronic conditions. Exercise and Chronic Disease: An Evidence-Based Approach offers the most up-to-date survey currently available of the scientific and clinical evidence underlying the effects of exercise in relation to functional outcomes, disease-specific health-related outcomes and quality of life in patients with chronic disease conditions.